Simulation of the self-healing of dolomitic lime mortar - Lubelli, Barbara (Materiali in tehnologije, 2012)
A test procedure was set up to reproduce laboratory self-healing on lime-based (both pure calcium and magnesium-calcium) mortar specimens. After a few months of testing, during which time the specimens were submitted to wet-dry cycles, thin sections of the specimens were prepared and observed using a polarization and fluorescence microscope (PFM) and a scanning electron microscope (SEM) equipped with an energy-dispersive X-ray spectrometer (EDX). The specimens prepared with dolomitic lime showed the occurrence of self-healing: a magnesium compound was observed to be filling the cracks and voids. These results suggest new possibilities for the development of dolomitic lime mortars with an increased self-healing capacity.
Keywords: samopoprava; self-healing; dolomitic mortar; dolomitna malta; microstructure; apnena malta; mikrostruktura